Investigating the origin of the spectral line profiles of the Hot Wolf–Rayet Star WR 2. Issue 4 (11th February 2019) - Chené, A-N; St-Louis, N; Moffat, A F J; Schnurr, O; Crowther, P A; Wade, G A; Richardson, N D; Baranec, C; Ziegler, C A; Law, N M; Riddle, R; Rate, G A; et al.
ABSTRACT: The hot WN star WR 2 (HD 6327) has been claimed to have many singular characteristics. To explain its unusually rounded and relatively weak emission line profiles, it has been proposed that WR 2 is rotating close to break-up with a magnetically confined wind. Alternatively, the line profiles could be explained by the dilution of WR 2's spectrum by that of a companion. In this paper, we present a study of WR 2 using near-infrared AO imaging and optical spectroscopy and polarimetry. Our spectra reveal the presence of weak photospheric absorption lines from a B 2.5–4V companion, which however contributes only 5–10 per cent to the total light, suggesting that the companion is a background object. Therefore, its flux cannot be causing any significant dilution of the WR star's emission lines. The absence of intrinsic linear continuum polarization from WR 2 does not support the proposed fast rotation. Our Stokes V spectrum was not of sufficient quality to test the presence of a moderately strong organized magnetic field but our new modelling indicates that to confine the wind the putative magnetic field must be significantly stronger than was previously suggested sufficiently strong as to make its presence implausible.